Plan estratégico de las relaciones humanas y públicas, en el entorno laboral de la Cooperativa de Ahorro y Crédito Ambato en el cantón Latacunga periodo académico 2014 - Caisaguano Guala, Sandra Viviana (2015)
The research helped to identify bad relationships that exist between the personal and customers of the Saving and Credit Ambato Cooperative, nowadays people are losing human values, because the society does not practice the values and this affects the relationship that stays with customers, to identify gaps that exist in the Cooperative staff has been applied interview and survey, this methods helped to know the importance of human relationships that should exist in the cooperative to improve its labor acting. The elaboration of a Strategic Plan is transcendental in the Saving and Credit Ambato Cooperative, also the application of values is important into practice inside of and outside of labor area that it will be of benefit for the cooperative. The human and public relationship in a cooperative are necessary in order to improve the qualities of the human talent, enlarging the knowledge and guiding client's good service, where can strengthen the corporate image. The obtained results allowed us the proposal planning, orientation and execution.